Lewis-pair-catalytic depolymerization of post-consumer polyethylene terephthalate (PET) waste - Killinger, Lukas; Hanich-Spahn, Ronny; Flick, Klemens; Hashmi, A. Stephen K. (Polymer degradation and stability, 2025)
Polyethylene terephthalate PET is one of the most used plastics in the world. Its main application lies in the packaging sector. Solely in 2022 in the EU 5 million tons of PET has been used in packaging. Since most packaging materials are only single use, this high consumption leads to huge amounts of PET waste. Only half of this waste has been recycled in the EU in 2022. The main reason for this low rate is the lack of suitable recycling technologies for mixed heterogeneous packaging waste streams. Within this work we investigated the glycolysis of PET as a recycling technique suitable for mixed waste streams. We present different Lewis pairs as catalysts for this recycling technology with excellent results for conversion and yield of the reaction. In addition, computational simulations were conducted to understand and evaluate the reactivity of different catalytic systems. The optimized systems were tested for the recycling of heterogeneous post-consumer waste and produced pure monomers in good yields. Overall, the investigated method is a promising technique for the recycling of post-consumer PET-waste.
Online veröffentlicht: 1. Januar 2025, Artikelversion: 10. Januar 2025
Gesehen am 31.07.2025